MEKANISME RESPON STRES: KONSEPTUALISASI INTEGRASI ISLAM DAN BARAT - Syahidah Rena (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
Essentially, stress is a prevalent event used to occur. Nowadays, the society experienced stress as an attribute of modern life, since it became an inevitable part of human’s life. Causally, stress appeared as an individual's response to stressors that are perceived as causing threat both internal and external balance disorders.This paper aimed to discuss stress phenomena and individual’s response mechanism to stress based on integrative perspectives of Western and Islam. As a library study, this research used a qualitative approach. Furthermore the study analyzed main sources of literature such as books, journals and various researches related to the topic. This study discovered that good stress/eustress which was explained in western psychological concept would give positive effect such as fostering tough personality was consistent to the message of Qur’an which explained that stress is a natural state in human life.Allah has created human beings having anxiety and complaint as a natural reaction of the body's system sensitivity towards unpleasant things. Within islamic perspective, stress which was organized with positive spirit could turn body condition became better and stronger.